(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Il repertorio autentico - 2. La questione gregoriana - 3. Cenni sulla notazione sangallese - 4. La restaurazione gregoriana. Gregorian chant: uniformity versus plurality ABSTRACT: From the earliest literary sources, Gregorian chant appears as the result of a great reflection on the sacred texts in an organic and unitary project that covers the entire liturgical year. To each celebration are addressed properly a text and a melody in a precise and unchangeable form because every piece represents a source of references that are part of a rigorous and codified plan. The textual and melodic unity of the Gregorian repertoire, realized in the Carolingian era through a process of hybridization between the ancient Roman chant and the Gallican chant, became a stabilizing factor in the political and religious unification of Europe in the ninth century, determining the end of liturgical regionalism. The wholeness of the repertoire is confirmed by the primitive musical notation, which fixes on parchment a previous oral tradition originating from a common matrix. The long period of decadence that had compromised the intelligibility of the original monody was followed by the colossal work of Solesmes, which allowed the reconstruction in its beauty and integrity. The subsequent ’typical editions’ of Gregorian chant were declared normative and pointed to by Pio X as an ultimate pattern for the whole Church.